Continuous ambulatory peritoneal dialysis after the honeymoon: review of experience in Newcastle 1979-84. Issue 6552 (11th October 1986) - Heaton, A; Rodger, R S; Sellars, L; Goodship, T H; Fletcher, K; Nikolakakis, N; Ward, M K; Wilkinson, R; Kerr, D N
Abstract : Two hundred and twenty nine consecutive patients (129 men, mean age 45) were reviewed 12 to 65 months after starting treatment with continuous ambulatory peritoneal dialysis (CAPD) from January 1979 to December 1983. They received CAPD for a mean of 19.8 (range 0.5-62) months. Actuarial patient survival was 79% at 24 months and 72% at 36 months. Half of the 46 deaths were related to cardiovascular disease, while eight patients died of abdominal complications, including three patients with peritonitis. Peritonitis occurred at a rate of one episode per 35 patient weeks, and 88% of episodes were cleared by one or more courses of antibiotics. This still left peritonitis as the commonest cause of failure of CAPD, leading to a permanent change of treatment in 44 patients and temporary interruption in a further 25. CAPD remains a reasonable medium term treatment in chronic renal failure. Despite the persisting problem of peritonitis the results are comparable with those achieved by haemodialysis, and CAPD has become the treatment of first choice for end stage renal failure in Newcastle. In younger patients judged unsuitable for transplantation and facing long term dialysis, however, haemodialysis is preferred.